Управление на растителните остатъци чрез обработката на почвата - Иван Димитров (Почвознание, агрохимия и екология, 2011)
The problem with the crops residues of the field production is one of the main important in the technology for the obtaining of agricultural production. As soon as the accelerated tendency for impoverishment оf the soils in the cultivated areas of organic substance is concerned we need technical solutions for utilization of plant residues. The soil cultivation controls the depth of the the residues incorporation into the soil and the speed of their decomposition. The purpose of the report is to generalize the results of the analysis of the seam distribution and the speed of decomposition of the plant residues of wheat and maize in dependence on the applied soil cultivation. Through the investigation we determined that at the most favorable depth for ploughing of plant residues is 10-30 сm, оn the average of 3 years 62.02% - 67.17% of the ploughed residues fall among. After a direct sowing for the whole rotation remains the biggest part of the residues in the superficial layer — 10 сm and it is more the 70%. When there is a soil distinction — an object of the study the accumulation of considerable qualities of plants residues in the superficial layer is not recommendable.